Distance-assistant node coverage identification model for wireless sensor networks - FAN Gao-juan1; SUN Li-juan1; WANG Ru-chuan1; HUANG Hai-ping1 (Tongxin xuebao)
A distance-assistant node coverage identification model was proposed which adopts distance information be-tween the node and its neighbors to identify nodes coverage without using any location information.Theory analysis and simulation results are presented to evaluate the proposed DANCI model.It is shown that in randomly deployed sensor networks,the maximum error between DANCI model and location information-aware strategy is 6.396 0%,and the nodes coverage accuracy improves significantly compared to neighbor number-based scheme and nearest neighbor-based scheme.